Complex minoxidil and platelet-rich plasma therapy effectiveness and its impact on physical performance - Paulina Cuper; Piotr Pawłucki; Anna Maciak; Michał Andrzej Kozicz; Ilona Jastrzębska; Krzysztof Bilecki; Hubert Gugulski; Michał Bado; Patrycja Nowoświat; Michał Sekuła (Nicolaus Copernicus University in Toruń, 2024)
Background Minoxidil and platelet-rich plasma (PRP) are proven treatments for androgenetic alopecia, however their combined therapy is not as researched. Research materials and methods Materials used for our research consist of published papers that pertain to both minoxidil and platelet-rich plasma therapies. More comprehensive papers, such as those including other substances were also included although results about other substances were not included, we simply discarded them. Each of the found and chosen articles were added and processed by various formulas which aim were to calculate efficacy of combined therapy while minimizing the errors and biases that could prop up in the source papers. Overall goal was to consolidate knowledge of the efficacy of combined therapy of minoxidil and platelet-rich plasma with emphasis on effect that could affect the physical performance. Results All trials have shown statistically significant improvement when compared to minoxidil monotherapy. Compared to PRP monotherapy results had been superior although not always in statistically significant manner. No trials have shown additional, adverse interactions, side effects or impacts on physical performance beyond those expected from the monotherapies, proving combined is as safe as monotherapies. Conclusion Combined therapy is proven to yield better results, while remaining a safe and cost-effective method. It doesn't impact physical performance in any way if taken correctly. Still higher quantity of research is welcome to make those finding more stable and in order to better assess the positive effect of combing titular substances.